2005
DOI: 10.2140/agt.2005.5.463
|View full text |Cite
|
Sign up to set email alerts
|

On hyperbolic 3–manifolds realizing the maximal distance between toroidal Dehn fillings

Abstract: For a hyperbolic 3-manifold M with a torus boundary component, all but finitely many Dehn fillings on the torus component yield hyperbolic 3-manifolds. In this paper, we will focus on the situation where M has two exceptional Dehn fillings, both of which yield toroidal manifolds. For such situation, Gordon gave an upper bound for the distance between two slopes of Dehn fillings. In particular, if M is large, then the distance is at most 5. We show that this upper bound can be improved by 1 for a broad class of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Suppose Δ(α, β) = 5. Then, we showed that ∂M is a single torus or two tori [6]. By [14], the latter case happens only when M is the Whitehead sister link exterior.…”
Section: Proofs Of Main Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Suppose Δ(α, β) = 5. Then, we showed that ∂M is a single torus or two tori [6]. By [14], the latter case happens only when M is the Whitehead sister link exterior.…”
Section: Proofs Of Main Resultsmentioning
confidence: 93%
“…If not, Δ(α, β) = 5 [7]. By [6], ∂M is a single torus or two tori. However, the latter case does not happen by [14].…”
Section: Proofs Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations